Dampak sosial media terhadap interaksi sosial pada remaja: Kajian sistematik - al-fikri, moh fatih (Maliki Interdisciplinary Journal, 2025)
This article presents a systematic analysis of articles published from 2011 to 2021 that specifically examine the impact of social media on interpersonal interactions. We used data from Google Scholar and articles published in SAGE and Sciencedirect. Data from various sources were analyzed using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) method. Based on the analysis, social media can be useful for women and students to develop themselves, access new information, increase knowledge, and reduce loneliness. However, this also has an impact on the mental health of the surrounding community.